Effect of L-carnitine administration to pregnant mice on some reproductive hormones and organs - K., Flayyih, N.; M-R., Fakhrildin, M-B. (The Iraqi Journal of Veterinary Medicine, 2012)
Carnitine is quaternary ammonium compound and required for the transport of fatty acids from the cytosol into the mitochondria for the generation of metabolic energy. The aims of the present study were to assess the effects of L-carnitine administration to pregnant mice on some parameters of reproductive performance and pregnancy outcome.One hundred and five pregnant female mice Swiss albino strain mice age: 12-14 weeks were used in this study. Pregnant mice were divided randomly into three equal groups including control group (administered distilled water; DW), low dose group (T1) administered 0.5 mg/Kg L-carnitine and high dose group (T2) administered 1 mg/Kg L-carnitine. Daily administration of D.W. or L-carnitine was continued from day 1 (day post-sexual mating) until parturition. Hormone assay involving follicle stimulating hormone (FSH), luteinizing hormone (LH) and estradiol (E2), litter size, percentage of female sex, weight of the reproductive system and endometrial thickness were assessed.Assessment of levels of serum reproductive hormones appeared that the FSH and LH and E2 for both treated groups were increased significantly (P<0.05) as compared to the control group. Moreover, significant increment (P<0.05) in the weight of reproductive system, litter sizes and a significant increment (P<0.05) in the thickness of endometrium for both treated groups was observed as compared to the control group.Conclusion: administration of 0.5 mg/Kg L-carnitine to pregnant mice had beneficial effects on pregnancy and offspring outcomes.